2015
DOI: 10.1186/s12862-015-0455-5
|View full text |Cite
|
Sign up to set email alerts
|

Tracing reinforcement through asymmetrical partner preference in the European common vole Microtus arvalis

Abstract: BackgroundThe mechanistic basis of speciation and in particular the contribution of behaviour to the completion of the speciation process is often contentious. Contact zones between related taxa provide a situation where selection against hybridization might reinforce separation by behavioural mechanisms, which could ultimately fully isolate the taxa. One of the most abundant European mammals, the common vole Microtus arvalis, forms multiple natural hybrid zones where rapidly diverging evolutionary lineages me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
(71 reference statements)
1
12
1
Order By: Relevance
“…Beysard and Heckel (2014) concluded that the divergence times between lineages play an important role in the level of gene introgression between them. A recent study by Beysard et al (2015) demonstrated that female common voles from the Western mtDNA lineage preferentially selected males from their own lineage under lab conditions in preference to Central lineage males. At present, we do not know if there is such a preference between voles of the Central and Eastern lineages present in Poland (which diverged more recently than the Central and Western lineages; Stojak et al 2015) or between lineages in the field vole (Beysard et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Beysard and Heckel (2014) concluded that the divergence times between lineages play an important role in the level of gene introgression between them. A recent study by Beysard et al (2015) demonstrated that female common voles from the Western mtDNA lineage preferentially selected males from their own lineage under lab conditions in preference to Central lineage males. At present, we do not know if there is such a preference between voles of the Central and Eastern lineages present in Poland (which diverged more recently than the Central and Western lineages; Stojak et al 2015) or between lineages in the field vole (Beysard et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to a number of precopulatory behavioural traits (Giesen et al, 2017), we obtained only weak evidence for such reinforcement in sympatric areas (the Swiss Alps) for the (postcopulatory) fecundity traits assessed here (egg production only). It thus appears that precopulatory behavioural traits, which are inherently plastic and can potentially evolve fast, are of overriding importance in preventing hybridisation in nature in this and other systems (Eberhard, 1996;Puniamoorthy, 2014;Puniamoorthy et al, 2009;Beysard, Krebs-Wheaton, & Heckel, 2015;Schmidt & Pfennig, 2016).…”
Section: Comparing the Biogeographic Cross-typesmentioning
confidence: 99%
“…4; see also While et al 2015). This explanation for sexual isolation asymmetry does of course not exclude other models, such as asymmetric postzygotic isolation (Alipaz et al 2005a, b), reinforcement (Coyne and Orr 2004), female preferences for heterospecific males (Ryan and Wagner 1987;Pfennig 2007;Beysard et al 2015), genetic drift (Kaneshiro 1980), sex differences in species recognition , or a transient stage in Fisherian runaway sexual selection (Arnold et al 1996).…”
Section: Discussionmentioning
confidence: 93%
“…, b), reinforcement (Coyne and Orr ), female preferences for heterospecific males (Ryan and Wagner ; Pfennig ; Beysard et al. ), genetic drift (Kaneshiro ), sex differences in species recognition (Svensson et al. ), or a transient stage in Fisherian runaway sexual selection (Arnold et al.…”
Section: Discussionmentioning
confidence: 99%